Flow visualization over a circular planform wing - Suliman , M. M. Ali; Omar, Ashraf Ali; Syed Mohamed Ali, Jaffar (2013)
circular plan form wing at high Reynolds numbers has been carried out numerically. Commercial software STAR-CCM+ was used for the investigation. The numerical results were presented in terms of flow visualization, pressure over the wing, velocity contour and streamlines, lift and drag coefficients for angle of attacks ranging from 0˚ to 30˚ for Reynolds numbers of 55,0000. The results showed that the distribution of the pressure is dominated by vortices at high angle of attack. The results also showed there is a large separation region located on the trailing edge of the elevator and the cockpit region. It is evident from the study that this type of wing configurations plays a very important role in delaying or preventing the flow separation. The result showed a good agreement with available experimental data.